We learn to write by reading, but writing can make you smarter - Stephen Krashen (Ilha do Desterro)
My goal in this paper is to make Iwo points: Writing style does not come from writing or from direct instruction, but from reading. Actual writing can help us solve problems and can make us smarter. Writing Style Comes from Readino, A substantial amount of research strongly suggests that we learn to write by reading. To be more precise, we acquire writing style, the special language of writing, by reading. Hypothesizing that writing style comes from reading, not from writing or instniction, is consistent with what is known about language acquisition: Most of language acquisition lakes place subconsciously, not through deliberate study, and it is a result of input (comprehension), not output (production) (Krashen, 1982).